2020
DOI: 10.3390/ijerph17186859
|View full text |Cite
|
Sign up to set email alerts
|

Transition Trajectories: Contexts, Difficulties and Consequences Reported by Young Transgender and Non-Binary Spaniards

Abstract: The transition process can have a significant impact on young transgender and non-binary individuals (TNBI), especially regarding their mental health. As such, this study aimed to explore the encountered difficulties and expectations of 225 young adults, between 14 and 25 years old, who identify themselves as TNBI. Four different aspects were analyzed: difficulties related to the transition process; main current difficulties; if the current difficulties are due to the participants’ sexual orientation or gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…(2020), the trans people in the study mentioned that they did not receive family acceptance, and the family members rejected them. Some were even thrown out of their houses [ 21 ]. However, studies among the transwomen and transgender community in New York and California found that while many of the participants reported that their family members did not initially agree and accept their transition, over time, the rejection changed to a positive acceptance and family members became more supportive [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020), the trans people in the study mentioned that they did not receive family acceptance, and the family members rejected them. Some were even thrown out of their houses [ 21 ]. However, studies among the transwomen and transgender community in New York and California found that while many of the participants reported that their family members did not initially agree and accept their transition, over time, the rejection changed to a positive acceptance and family members became more supportive [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some may choose to undergo physical transformations by using hormonal therapy and surgery, while others may be satisfied with only one or the other [ 20 ]. Studies have shown transition leads to healthier self-image, lower depression rates [ 12 , 21 , 22 ] improved attitude towards life, extraversion, good stress coping ability, optimism, improved quality of life, self-reported well-being, social relationships, elevated self-esteem, and body image [ 12 , 20 , [23] , [24] , [25] , [26] , [27] ]…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 convenience study found participants who experienced COVID-19-related stress reported consuming significantly more drinks and a greater number of drinking days. Thirty-four percent of those who reported increased drinking identified greater availability as the cause [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential importance of supportive social relationships to transgender health and well‐being, relatively few studies have examined the intricacies of social relationships for transgender people and their relational partners, aside from a few that focus on specific health behaviors, such as sexual health behaviors (e.g., pre‐exposure prophylaxis usage), and in specific relational clusters, such as with parents (Biblarz & Savci, 2010; Hines, 2006; Mehrotra et al., 2018). As mentioned previously, it is uncommon for research on this topic to include more than one perspective on relationships, which leads to limitations in terms of reporter biases and the extent to which specific issues are echoed by various parties (Biblarz & Savci et al., 2010; Hines, 2006).…”
Section: Introductionmentioning
confidence: 99%